Contrasting influence of flow regime on freshwater fishes displaying diadromous and nondiadromous life histories. Issue 1 (5th September 2012) - Crow, Shannan K.; Booker, Doug J.; Snelder, Ton H.
Abstract Flow variability structures freshwater fish community traits and life‐history patterns such as migration patterns between fresh and saltwater (diadromy). Few studies, however, have explored relationships between diadromy and flow regime while accounting for other abiotic covariables. The present paper used canonical ordinations to remove the shared variation between groups of explanatory variables that explain variation in fish communities and examine two objectives with New Zealand fishes: (i) to compare the unique contributions of Hydrological Regime, Climate, Habitat and Spatial‐Seasonal data sets to the variation of diadromous and nondiadromous fishes and (ii) to compare the relative contributions of a Hydrological Variability and Low‐Flow data set to community structure of both life‐history patterns. All explanatory variables explained a total of 20.15% and 29.58% of the variation in diadromous and nondiadromous fishes, respectively. Objective 1 analyses showed that the largest unique component of variation was explained by Hydrological Regime for nondiadromous fishes (12.17%), while Climate uniquely explained the most variation in diadromous fishes (4.3%), followed closely by Hydrological Regime (3.08%). Objective 2 analyses showed that Hydrological Variability uniquely explained five and 11 times more variation than the Low‐Flow data set in diadromous and nondiadromous fishes, respectively. Findings illustrate the importance of hydrological regime to New Zealand freshwater fishes. Specifically, aspects of hydrological variability uniquely account for more variation than aspects of low flow. Differing relative influences of hydrology between life‐history patterns suggest that diadromy may mediate the influence of flow regime. Results outline difficulties for environmental flow settings when biota display differing life histories.